Burnout syndrome (BOS) among resident doctors in an Egyptian tertiary care university hospital: Prevalence and determinants during the COVID-19 pandemic. (March 2023) - Fadle, Amr A.; Khalifa, Ahmed A; Mahran, Dalia G.; Khidr, Shimaa Sayed; Said, Hatem G; Farouk, Osama
Objectives: The current study aimed to detect the BOS prevalence and determinants among residents working during the second wave of the COVID-19 pandemic in an Egyptian tertiary university referral hospital. Methods: A cross-sectional study evaluating the working period from June to November 2020 during the COVID-19 pandemic second wave, through a five sections questionnaire evaluating: 1 − sociodemographic characteristics, 2 − job characteristics, 3 − negative thoughts related to their job, 4 − resident's health problems, and 5 − evaluating BOS through Maslach Burnout Inventory (MBI) scale (including emotional exhaustion [EE], depersonalization [DP], and personal accomplishment [PA] as subscales). Results: We included 230 residents with a median age of 27 years. The median MBI sub-scales (IQ Range) values were 30.0 (20, 39), 21.0 (15, 30), and 29.5 (22, 36) for EE, DP, and PA, respectively. About 51.0% and 83.0% of the residents were high in EE and DP, while 8.7% were low in PA. The median EE and DP were higher in younger age (⩽27 years; p  = .002 and .024), males ( p  = .001 and <.001), working >90 hours weekly ( p  = .016 and <.001), exposure to harassment ( p  < .001), and having COVID-19 infection ( p  = .002 and .001). Residents working in surgical departments reported higher DP scores than those in non-surgical departments ( p  = .03). There was a mild positive correlation between working hours per week and the total scores in EE and DP, r  = .24 ( p  < .001) and r  = .23 ( p  = .001) respectively, while it was found to have a negative correlation with the PA ( r  = −.133 and p  = .044). Conclusions: The BOS is evident and considerably high among the residents working during the COVID-19 pandemic. Younger age, males, working in surgical departments, and those who got COVID-19 infection were most vulnerable.